Can Strikes Pay for Management? Pro Sports’ Major Turnarounds - Fisher, Edward (Relations industrielles / Industrial Relations, 2007)
Collective bargaining and antitrust law emancipated players. The advent of free agency and related contractual provisions created a battle line over splitting revenues. Work stoppages can foster players’ resisting or employers’ enforcing “salary restraint mechanisms.” Each major sport had a major showdown and corresponding turnaround in “survival bargaining.” My framework adds “litigious and other maneuvers” as backups to the traditional strategic choices of “reconfiguring” versus “forcing” or “resisting change.” It expands on Walton and McKersie’s “sanction as an investment device,” “intra-organizational bargaining,” and “attitudinal structuring” (1965). In each major turnaround management eventually achieved a stable contractual formula consistent with a three-pronged formula: (1) demonstrate a performance gap, (2) play on worst fears via sanctions or their threat, and (3) provide incentives to settle or change.